Theory of International Regimes (Czech Journal of International Relations, 2002)
The analysis of international regimes has its origins in the United States of the 1970s. It arose as an effort to explain the international developments of this period, like the decline in the hegemonic position of the US, détente in Europe, and the rise of cooperative alignments. The theory of international regimes should be understood as a liberal attempt to explain international cooperation at the system level. The analysis of international regimes (like other theoretical approaches) is based on the empirical observations available to the analysts and which they themselves regard as relevant. As a result of this fact, there is a difference between European and American analyses of international regimes.The analysis of regimes makes use of various theories and approaches to explain the myriad phenomena in the sphere of international politics (e.g. the rise, duration, and fall of regimes). Thus far the strongest school of thought in the analysis of international regimes has been put forth by neoliberal institutionalism, but today we are witnessing, particularly in Europe, a new integrative approach in the analysis of international regimes, derived from the American neo-neo synthesis.According to the theory of international regimes, regimes are cooperative structures assembled from common principles, norms, rules, and procedures, and are focused toward a certain thematic area (specific cooperative institutions). The definition of international regimes partially overlaps with that of international organizations and conventions, but regimes are not identical to these other entities. Regimes enable their members to more easily orient themselves in an interdependent world, both in terms of foreign and domestic policies. For example, regimes lower their members' costs of information gathering and thus reduce their uncertainty in the international system. This uncertainty decreases with the formulation of rules, norms, and principles, which make the members' behavior more predictable and regulate expectations.In today´s world of international politics, international regimes are - for all the problems they face - a means for coordinating the actors' political and social behavior and a clear source of power for their member states.